Analysis of the Characteristic Value of Jepara Batik Carving Motifs as a Charge of Fine Arts Education - Furqon, Muhamad Nailul; Wijayanto, Wasis (Jurnal Prajaiswara, 2024)
Abstract—Introduction/Main Objectives: This article aims to explain the character values found in batik, which focuses on Jepara batik. Research Methods: this article uses a research method with a descriptive qualitative research type and a hermeneutic approach. The samples are batik motif lung gunung, motif lung cinta jepara, motif lung ngrembaka, motif lung merak and motif lung wuni. This article uses data collection techniques including literacy studies, documentation, interviews and observation. In the part of the interview that was conducted was freely guided, so the data collection was only with an outline in terms of interviewing the sources. Meanwhile, the data obtained in this article is analyzed with descriptive qualitative. Finding/Results: This article has the result of describing the five motifs of Jepara carving lung-lungan there are character values and these character values can be used as a means to form character in every student at school.